An examination of caregiver incarceration, positive childhood experiences, and school success. (February 2022) - Crouch, Elizabeth; Smith, Hayden P.; Andersen, Tia Stevens
Highlights: Children of incarcerated caregivers may be at higher risk for challenges to school success. The quantification of positive childhood experiences (PCEs) is important to determine as children of incarcerated parents are less likely to experience many PCEs. Programs to support PCEs among children of incarcerated parents may help to reduce the impact of household incarceration on children. Abstract: Positive childhood experiences (PCEs) foster healthy child development. Yet little is known about the degree to which children of incarcerated parents are exposed to positive childhood experiences (PCEs), such as participation in after-school activities, volunteering in the community, and residing in a safe and supportive neighborhood. We analyzed 2017–2018 data from the National Survey of Children's Health to examine the relationship between caregiver incarceration and two academic outcomes, repeating a grade and school absenteeism, controlling for child and caregiver characteristics, and to examine the relationship between caregiver incarceration and PCEs, controlling for child and caregiver characteristics. Children exposed to household incarceration had higher odds of repeating a grade than children not exposed to household incarceration (aOR 1.62; 95% CI 1.23–2.13). Children with exposure to household incarceration had lower odds of residing in a supportive neighborhood than children without exposure to household incarceration (aOR 0.77; 95% CI 0.64–0.93). Findings from this study can be used by policymakers and program developers in the development and implementation of programs for children with incarcerated parents.